2012
DOI: 10.1155/2012/863747
|View full text |Cite
|
Sign up to set email alerts
|

Optical Imaging in Breast Cancer Diagnosis: The Next Evolution

Abstract: Breast cancer is one of the most common cancers among the population of the Western world. Diagnostic methods include mammography, ultrasound, and magnetic resonance; meanwhile, nuclear medicine techniques have a secondary role, being useful in regional assessment and therapy followup. Optical imaging is a very promising imaging technique that uses near-infrared light to assess optical properties of tissues and is expected to play an important role in breast cancer detection. Optical breast imaging can be perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(45 citation statements)
references
References 49 publications
0
44
0
1
Order By: Relevance
“…Moreover, optical imaging is relatively cheap and imaging agents are easier to generate than PET tracers. As for the depth penetration issue in optical imaging, using NIR light and advanced more sensitive detection equipment, penetration depth in human tissue is now possible up to 15 cm (Herranz and Ruibal 2012). The result in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, optical imaging is relatively cheap and imaging agents are easier to generate than PET tracers. As for the depth penetration issue in optical imaging, using NIR light and advanced more sensitive detection equipment, penetration depth in human tissue is now possible up to 15 cm (Herranz and Ruibal 2012). The result in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…39 While the fusion of optical or photoacoustic imaging with other more quantitative imaging modalities can compensate for the low spatial resolution of PET or SPECT imaging, NIRF imaging remains limited by its low depth penetration, attenuation caused by overlapping tissues, and lack of quantitative methods for signal quantification. 40 …”
Section: Discussionmentioning
confidence: 99%
“…The errors in Dl a at the depths of 5 and 7 mm were 3 and 20% of the true Dl a , respectively. When a real cancer lesion with high concentrations of hemoglobin or contrast agents had l a larger than the background normal tissues as reported in the literature [9][10][11][12][13][14][15], the error may not disturb the diagnosis. The literature showed that the l a of cancer tissue was 2 -4 times as large as the l a of normal tissue.…”
Section: Although Some Mismatches In Cmentioning
confidence: 95%
“…The absorption coefficient of the photon absorber can reflect the conditions of biological tissues. Angiogenesis in cancer tissues increases the concentration of hemoglobin, which increases the absorption coefficient [9][10][11][12][13][14][15]. Some contrast agent molecules and nanoparticles increasing the light absorption coefficient are useful for finding diseased tissues [16,17] and mapping the sentinel lymph nodes [18,19].…”
Section: Introductionmentioning
confidence: 99%